Pengaruh Kepercayaan Diri Terhadap Prestasi Belajar Matematika Siswa SMP Negeri 1 Buton Tengah - Herlawan Herlawan; Ernawati Jais; Hadijah Hadijah (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The formulation of the problem in this research was whether there was an effect of self-confidence on the mathematics learning achiavements of VIII grade students of SMP Negeri 1 Buton Tengah?. The purpose of this research was to determine the effect of self-confidence on mathematics learning achievement of VIII grade students of SMP Negeri 1 Buton Tengah. This research was an ex-post facto research. The population in this research were all students of VIII grade as SMP Negeri 1 Buton Tengah which consisted of 5 classes. The sample was taken as much as 20% of the total population using random sampling tachniques at SMP Negeri 1 Buton Tengah. Data collection techniques in research used a questionnaire. Based on the result of calculations using simple regression, the linear regression equation was obtained: Y = 73.108 + 0.071X. with a t value of 0.528,it was significant at 0.602>0.05. This indicuted that H0 was accepted, or H1 was rejected. This meant that there was no effect of students self-confidence on students’ mathematics learning achievements at SMP Negeri 1 Buton Tengah.